Tutorial function in formal education system: a possible modalities classifi cation - Borgobello, Ana; Peralta, Nadia Soledad; Roselli, Néstor Daniel (Pensando Psicología, 2010)
In despite of the prolific literature about tutoring at different levels of education, there is a lack of agreements on unifi ed classifications around these tutorial mediations or functions. For this reason, it is proposed here a possible taxonomy with the goal of been enough comprehensive and with restrictedcategories. The classifi cation was made collecting different kind of data and empirical research papers. This analysis allowed establishing the following categories: peer tutors (with the same and with different degrees of preparation) and experts (counselors and teachers). The fi nal goal of this paper is to be useful for future studies in the area.
Keywords: tutoring; tutorial functions; tutorial mediations; formal education; taxonomy